Managerial issues in digital transformation of global modern corporations - Esakki, Thangasamy, 1970- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
""This book explores the prospects and challenges of the digital transformation of modern business corporations during the process of transition from the outdated business endeavors to the updated ones"--Provided by publisher"--